EVALUATION OF THE IMPLEMENTATION OF CHARACTER EDUCATION IN SCHOOL CULTURE - LUBIS, Kholilah (JKP | Jurnal Kepemimpinan Pendidikan, 2022)
This research aims to evaluate the implementation of character education in school culture at Pondok Bahar 5 Public Elementary School in terms of context, input, process, and product. This research method is a qualitative research method with the CIPP model. The results showed that in terms of context, character education planning was contained in the vision, mission, and goals of SD Negeri Pondok Bahar 5 which were then integrated into the curriculum. In terms of focus, the school provides support for all teachers and staff provided by the principal every three months, as well as supervision and support from the principal. In terms of the process, the implementation of character education at SD Negeri Pondok Bahar 5 has been as expected by the school, although in its implementation there are still obstacles. In terms of results, the evaluation of the character education program products illustrates that character education in the school culture at SD Negeri Pondok Bahar 5 has good results, even though there are obstacles in its implementation. The implementation of character education will be more efficient if there is good cooperation between the school and parents so that good habits carried out at school can also be applied at home.